Improved expression of secreted and membrane-targeted proteins in insect cells. - Hitchman, R; Possee, R; Siaterli, E; Richards, K; Clayton, A; Bird, L; Owens, R; Carpentier, D; King, F; Danquah, J; Spink, K; King, L (2010)
Secretory and membrane-bound proteins are generally produced in lower amounts in insect cells compared with cytoplasmic and nuclear proteins. There may be many reasons for this, including degradation of recombinant proteins by proteases, competition for cellular resources between native and recombinant proteins, and physical blockage of the secretory pathways. In the present study, we describe the construction of a baculovirus in which chiA (chitinase) and cath (cathepsin) genes have been deleted and show improved recombinant protein expression using this vector. We confirmed the complete removal of both genes by PCR, restriction enzyme analysis and enzyme assays, and the modified virus DNA was shown to be stable in bacterial cells over multiple passages. A selection of recombinant genes were inserted into the double-deletion virus and their expression levels compared with recombinant viruses that had single or no gene deletions. In all instances, the double-deletion viruses showed greatly enhanced levels of protein production for both secreted and nuclear/cytoplasmic proteins. In summary, we have conclusively demonstrated the importance of this deletion vector for the high-level production of recombinant proteins.